Focus on personal finance : an active approach to help you develop successful financial skills - Kapoor, Jagdish R. , 1937-; Dlabay, Les R.; Hughes, Robert James , 1946 (The McGraw-Hill/Irwin series in finance, insurance and real estate, 2010)
Covers the critical topics in personal finance courses